2013
DOI: 10.4049/jimmunol.1201641
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Graft-versus-Host Disease and Graft-versus-Leukemia Responses Using TCR Vβ Spectratype Analysis in a Murine Bone Marrow Transplantation Model

Abstract: The optimum use of allogeneic blood and marrow transplantation (BMT) as a curative therapy for hematological malignancies lies in the successful separation of mature donor T cells that are host-reactive and induce graft-versus-host disease (GVHD) from those that are tumor-reactive and mediate graft-versus-leukemia (GVL) effects. To study whether this separation was possible in an MHC-matched murine BMT model (B10.BR→CBA) with a CBA-derived myeloid leukemia line, MMC6, we used TCR Vβ CDR3-size spectratype analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 54 publications
1
14
0
1
Order By: Relevance
“…In region D the decrease was of 26.16%, whereas the entire MFI shifted 41.93%. CD8 þ T cells [22], we studied specifically the response of CD8 þ B10.BR T cells in MLCs against ONX 0914 or PR-825etreated CBA splenocytes and confirmed that only LMP7-specific inhibition led to a decreased production of IFN-g by this population (Figure 4). …”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In region D the decrease was of 26.16%, whereas the entire MFI shifted 41.93%. CD8 þ T cells [22], we studied specifically the response of CD8 þ B10.BR T cells in MLCs against ONX 0914 or PR-825etreated CBA splenocytes and confirmed that only LMP7-specific inhibition led to a decreased production of IFN-g by this population (Figure 4). …”
Section: Discussionmentioning
confidence: 67%
“…Although to the best of our knowledge there has been no study demonstrating the LMP7-dependency of the OVA257e264 epitope, we decided to use splenocytes from transgenic B6-SIINFEKL mice because this peptide is known to generate CD8 þ T responsesdthe population largely responsible for GVHD in the B10.BR/ CBA model [22]. Interestingly, we found that the percentage decrease of SIINFEKL expression peaked at 24 hours after a 1-hour exposure to ONX 0914 and that this decrease was less prominent by 48 hours (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…The adoptive transfer of miHA-specific CTLs selected on the basis of recognition of recipient hematopoietic cells but not skin fibroblasts has also unexpectedly been associated with GVHD. Likewise, in a murine model of BMT, infusion of tumor-specific CTLs identified by CDR3-size spectratype analysis was shown to induce a significant GVT response, but the same tumor-reactive Vβ family, which initially showed no hematopoietic alloreactivity was ultimately the causal entity of gut pathology in recipient mice, when administered at higher dosages [68]. Taken together, the results from these clinical trials and murine models suggest that responses to target tissue–related miHA are complex and may vary not only amongst different individuals but also between tissue types.…”
Section: Classification Of Tumor Antigensmentioning
confidence: 99%
“…The Vβ13 family was shown to be highly skewed in the B10.BR CD8 T-cell response against a myeloid leukemia cell line (MMC6), but not in the alloresponse against CBA recipient mice. Transplantation of low doses of CD8 + Vβ13 + T cells, isolated by magnetic cell separation, induced a slight GvT response with no concomitant acute GvHD development [24]. In the B6→Balb.b (MHC-matched) GvHD response, several Vβ families have been found to be skewed within CD4 T cells.…”
Section: Discussionmentioning
confidence: 98%